RESPONSIVE GOVERNANCE DALAM PENGEMBANGAN PORTAL SEMARANG SATU DATA DI DINAS KOMUNIKASI INFORMATIKA STATISTIK DAN PERSANDIAN KOTA SEMARANG - Audrey Al Fahri, Aulia; Santoso, R. Slamet; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
The issuance of Presidential Regulation Number 95 of 2018 concerning Electronic- Based Government Systems (SPBE) is a new challenge for the government to provide fast and accurate services because the use of information and communication technology (ICT) will make information systems within local governments connected online so that people can obtain services that are fast, precise, easy, and cheaper. Basically the implementation of using websites in government services aims to improve public services by being more responsive to the public through online-based websites. The problem in this study is the absence of a two-way feature and the government's lack of responsiveness in managing the Semarang One Data Portal which causes a lack of community participation in its development. The purpose of this study is to analyze Responsive Governance in the development of the Semarang One Data Portal and to find out the determinants of the success of Responsive Governance in the development process of Semarang One Data at the Office of Communication, Statistical Informatics and Encryption of Semarang City with reference to the theory of Responsive Governance by the Agus Dwiyanto, 2008. Methods This research is descriptive using a qualitative approach and the informants were taken from the Semarang City Communication Informatics and Coding Service.